PENGARUH MODEL PEMBELAJARAN RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMAN 1 SULIKI - Yahya, Muthia Alayda (Departemen Matematika, 2024)
Class XI pupils at SMA Negeri 1 Suliki still have room to grow academically. The learning model that is employed during the learning process is one of the aspects that impact the final product of the learning. The REACT Learning Model—which stands for